Realization of an in-situ Fluorescence & Raman Spectroscopy Setup for studying Quantum Dot Films - Dijkema, Jurgen (Student Undergraduate Research E-journal!, 2018)
A new experimental setup for studying charge transfer in Quantum Dot (QD) films has been designed, built and tested. The setup combines three spectroscopic methods; Raman, Fluorescence and Absorption Spectroscopy. First data on a Cadmium Selenide (CdSe) films reveals that radiative emission quenches while charging, attributed to Auger-decay. When fully discharged, the emission remains partly quenched, indicating that not all electrons are removed. Since charge transfer is a fundamental process in solar cells, the setup could be essential for designing and optimizing cost efficient future QD based solar cells.